Effective Pedagogical Approaches in Fostering Student Responsibility: A Qualitative Study at an Islamic Boarding School in Indonesia - Sari , Lusi Kemala; Hartati , Zainap; Khalfiah , Yuliani; Halid , Yusrin (Universitas Muhammadiyah Surakarta, 2025)
Student responsibility attitudes are important in shaping character and discipline in school. Teachers play a big role in fostering this attitude through the right approach. At SMA Terpadu Islam Hasanka Boarding School Palangka Raya, the teacher's approach is the key to increasing student responsibility for regulations in school activities. This study aims to describe the teacher's approach in improving students' attitude of responsibility at SMA Terpadu Islam Hasanka Boarding School, Palangka Raya. This research uses a qualitative method. The subjects of this study are two teachers, consisting of 1 teacher of Moral Faith and one teacher of Islamic Religious Education. Meanwhile, the informants in this study are the principal, vice principal for student affairs, and students. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out qualitatively through four stages: data collection, data reduction, data presentation, and drawing a conclusion. The results of this study show that students of Hasanka Boarding School Palangka Raya Integrated Islamic High School generally have an attitude of responsibility towards school regulations, both in learning activities and outside of learning. In the classroom, students tend to complete assignments on time, be active, and be ready to learn, although some are still inconsistent. Outside of the classroom, students are quite disciplined in participating in activities such as congregational prayers, Qur'an halaqah, ceremonies, and extracurricular activities, although some have not fully complied with the rules of attributes. Teachers use persuasive, communicative, and personal approaches through example and guidance to foster student responsibility. This approach has proven to be effective in shaping students' attitudes of discipline and compliance with school rules.